Effectiveness of Guava Leaf Extract (Syzygium Aqueum) in Inhibiting The Growth of Bacteria Aggregatibacter Actinomycetemcomitans - Sudrajat, Attidhira Citra Lestari; Hardhani, Puspito Ratih; Sukmawati, Ayuda Nur; Arnov, Steffi Triany; Rimawati, Noor (South East Asia Nursing Research, 2021)
The role of Aggregatibacter actinomycetemcomitans bacteria can lead to the occurrence of aggressive periodontitis. The bacterium infects periodontal tissue with its virulence factor. Antibacterial administration such as chlorhexidine mouthwash is one of the treatments for periodontal disease due to bacteria. Long-term use of chlorhexidine can cause irritation of the oral mucosa, burning sensation, changes in taste perception and the appearance of stains on the teeth. One alternative is to gargle the guava leaf extract water. The antibacterial effect of guava leaf extract is obtained from its chemical compounds, namely flavonoids, phenolics, alkaloids, ethanol and tannins. This research aims to know the potential of water guava leaf extract (Syzygium aqueum) in inhibiting the growth of Aggregatibacter actinomycetemcomitans bacteria.  A literature review by reviewing research articles from Science Direct and Google Scholar using the keywords "Syzygium aqueum and Aggregatibacter actinomycetemcomitans".   Guava leaves contain many derivatives of compounds such as flavonoids, alkaloids, tannins, saponins, and terpenoids. The content of these compounds can be used as antibacterial because they are effective in inhibiting the growth of bacteria.  Water guava leaf extract (Syzygium aqueum) can inhibit the growth of Aggregatibacter actinomycetemcomitans bacteria.